Effect of Mitomycin C on Myopic versus Astigmatic Photorefractive Keratectomy - Ashwag A. Almosa; Samah M. Fawzy (Journal of Ophthalmology)
Purpose. Long-term mitomycin C (MMC) effects on photorefractive keratectomy (PRK) were compared in simple myopic and astigmatic patients. Methods. In this observational cohort study, subjects were selected based on preoperative and postoperative data collected from medical records; they were divided into simple myopia with/without MMC and myopic astigmatism with/without MMC groups. Haze, uncorrected visual acuity (UCVA), best-corrected visual acuity (BCVA), subjective refraction, and K-reading were evaluated at 1-, 3-, 6-, and 12-month follow-ups. Results. One hundred fifty-nine eyes of 80 subjects (34 women and 46 men; mean age, 26.81 ± 7.74 years; range, 18–53 years; spherical powers, −0.50 to −8.00 DS; and cylindrical powers, −0.25 to −5.00 DC) were enrolled. One year postoperatively, the simple myopia with/without MMC groups showed no difference in UCVA (P=0.187), BCVA (P=0.163), or spherical equivalent (P=0.163) and a significant difference (P=0.0495) in K-reading; the haze formation difference was nonsignificant (P=0.056). Astigmatic groups with/without MMC showed a significant difference in K-reading (P<0.0001). MMC groups had less haze formation (P<0.0001). Conclusion. PRK with intraoperative MMC application showed excellent visual outcomes. MMC’s effect on astigmatic patients was significantly better with acceptable safety and minimal side effects.